2005
DOI: 10.1002/jso.20232
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of circumferential margin involvement in rectal adenocarcinoma treated with preoperative chemoradiotherapy and low anterior resection

Abstract: In patients with rectal cancer treated by preoperative chemoradiation plus total mesorectal excision (TME) and sphincter saving surgery, circumferential margin involvement is associated with high incidence of distant recurrence and cancer-related death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 14 publications
2
29
0
1
Order By: Relevance
“…However, some researchers argued that CRM <2 mm was associated with a negative prognosis 18, 19, 20, 21, 22. A CRM clearance of >5 mm and 0.4 mm was proposed by Kelly et al1 in 2009 and Beaufrère et al23 in 2017, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some researchers argued that CRM <2 mm was associated with a negative prognosis 18, 19, 20, 21, 22. A CRM clearance of >5 mm and 0.4 mm was proposed by Kelly et al1 in 2009 and Beaufrère et al23 in 2017, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The criterion to define a positive CRM remains unclear. However, some researchers believed that CRM within 2 mm was associated with a negative prognosis 18, 19, 20, 21, 22. In addition, Kelly et al1 argued that a CRM clearance >5 mm should be achieved to optimize curative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…© 2007 American Association for Cancer clincancerres.aacrjournals.org Downloaded from samples collected from the fibrotic area was 9 (median, 7; range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Figure 1 shows representative examples of different degrees of tumor regression.…”
Section: Methodsmentioning
confidence: 99%
“…Wibe et al [10] reported that a positive circumferential resection margin has a significant and major prognostic impact on the local recurrence rate of rectal carcinoma after TME. However, Luna-Perez et al [19] reported that circumferential resection margin involvement is not correlated significantly with local recurrence of rectal adenocarcinoma (P = 0.33). Hall et al [11] reported that the local recurrence rate of rectal carcinoma with a positive circumferential resection margin is 15% and 11% in of those with a negative circumferential resection margin.…”
Section: Discussionmentioning
confidence: 97%
“…The correlation between circumferential resection margin status and local recurrence of rectal carcinoma is still controversial [10,11,[19][20][21] . Wibe et al [10] reported that a positive circumferential resection margin has a significant and major prognostic impact on the local recurrence rate of rectal carcinoma after TME.…”
Section: Discussionmentioning
confidence: 99%